Thermally oxidized MoS2-based hybrids as superior electrodes for supercapacitor and photoelectrochemical applications. (10th December 2022) - Rashidi, Marzieh; Ghasemi, Foad
Abstract: High electronic transport and reasonable chemical stability of molybdenum disulfide (MoS2 ) make it very suitable for electrochemical applications. However, its energy storage capacity is still low compared with other nanostructures. In this work, pristine and thermally oxidized MoS2 (O@MoS2 ) based hybrids are introduced by a simple method with enhanced capacitive performance thanks to the contribution of synergistic effects. Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), X-ray diffraction (XRD), elemental mapping, UV-Visible, Raman, X-ray photoelectron (XPS) spectroscopies and BET specific surface area analyses are employed to investigate the morphological and crystalline structure of the introduced hybrids. In detail, the highest gravimetric capacitance of ∼205.1 Fg −1 is achieved for the MoS2 :O@MoS2 hybrid with a mass ratio of 2:1 compared to pristine and other electrodes. This electrode is also accompanied by the longest discharging time and excellent cyclic stability of ∼%113 after 2000 continuous charge-discharge cycles. In addition, photoelectrochemical testing of the introduced electrode leads to a ∼63% increase in carrier photogeneration compared to MoS2 due to the effective charge separation within the hybrid, which makes it suitable for water splitting and hydrogen production applications. Graphical Abstract: Image, graphical abstract